PERSEPSI KEGUNAAN, KEAMANAN DAN KERAHASIAAN, KERUMITAN, PENGALAMAN DAN KESUKARELAAN MEMPENGARUHI MINAT WAJIB PAJAK DALAM MENGGUNAKAN E-FILING - Ita Tri Astuti, 13.05.52.0057; Nuswandari, Cahyani (Students Journal of Accounting and Banking, 2017)
This study aims to analyze perceptions of usefulness, security and confidentiality, complexity, experience and volunteers affect the interests of taxpayers in using e-Filing. The type of data used in this study is the primary data. Population in this research is Individual Taxpayer at KPP Semarang Selatan. Sampling was done by using Convenience sampling method and the number of samples were 110 respondents. The primary data collection method used is survey method by using questionnaire. Data obtained from the questionnaire were analyzed using multiple linear regression model. The results showed that perception of utility, security and confidentiality, experience and volunteer have a positive and significant influence to Taxpayers interest in using e-Filing, while the complexity has a significant negative effect on taxpayer interest in using e-Filing.Keywords:Â Perceived Usefulness, Security and Confidentiality, Complexity, Experience and Volunteer, Taxpayer Interest in Using e-Filing